Predicate formation and verb-stranding ellipsis in Uzbek. Issue 1 (28th December 2020) - Gribanova, Vera
This paper investigates the interaction between head movement of the verb and ellipsis of v P (verb-stranding ellipsis, VSE ) in Uzbek — an understudied Turkic language of Central Asia. I argue that Uzbek verbal predicates are formed by head movement, while non-verbal predicates are formed by a species of Local Dislocation (Embick & Noyer 2001 ;Embick 2003 ). Uzbek has two distinct ellipsis strategies that yield similar strings: argument ellipsis (AE ) andVSE .VSE occurs only with (head-moved) verbs, and can elide non-verbal predicates, whileAE cannot. UzbekVSE imposes a strict identity requirement on the heads extracted from the ellipsis site (the Verbal Identity Condition (Goldberg 2005b )). Both the genuine existence of this condition, and its source, have recently come under scrutiny; this paper presents Uzbek evidence in support of the claim that the Verbal Identity Condition is genuinely present in a subset of typologically diverse languages withVSE (seeGribanova 2018b ). Variable crosslinguistic behavior with respect to the Verbal Identity Condition is predicted by an independently supported view of head movement (Harizanov & Gribanova 2019 ) in which certain types of head movement are syntactic — yielding the potential for mismatches of extracted material, by analogy with phrasal movement (Merchant 2001 ) — while others are postsyntactic (yielding the Uzbek-typeVSE pattern). The Uzbek investigation therefore provides crucial evidence in favor of a particular view of the crosslinguistic landscape ofVSE, and moves us a step closer to explaining why head movement out of ellipsis domains varies systematically in its behavior across languages.